The echo of things: The lives of photographs in the Solomon Islands - Šimůnek, Michal (My University, 2015)
Review article of the book Wright, Ch. 2013. The echo of things: The lives of photographs in the Solomon Islands. Durham & London: Duke University Press.
The echo of things: The lives of photographs in the Solomon Islands
Keywords: visual ethnography, photography, memory; vizuální etnografie, fotografie, paměť